Location-based routing protocols in wireless sensor networks: a survey. (2014) - Soni, Vaibhav; Mallick, Dheeresh K.
Recent advances in micro electro-mechanical systems (MEMS), wireless sensor networks (WSNs) and digital electronics have provided low-cost, low-power, multi-functional but small in size sensors with capabilities of sensing various physical and environmental conditions, data processing and wireless communication within short range. In WSNs, sensors have limited power, processing, storage and communication capabilities. Hence, these networks require more effective and energy efficient schemes for routing of data and processing. In recent years, many location-based routing protocols have been proposed for WSNs where energy consideration is taken as an important constraint to extend the network lifetime. In this survey, we discuss the architecture of wireless sensor networks followed by challenges in designing routing protocols for these networks. Further, we present various location-based routing protocols proposed by numerous researcher and finally these protocols are compared on the basis of different parameters.